Injection-Triggered Occlusion of Flow Pathways in Geothermal Operations - Maren Brehme; Simona Regenspurg; Peter Leary; Fatih Bulut; Harald Milsch; Sigitas Petrauskas; Robertas Valickas; Guido Blöcher (Geofluids)
Reasons for injectivity decline were investigated in a low-enthalpy geothermal aquifer in Klaipeda (Lithuania). It is one of the study sites within the DESTRESS project, which demonstrates different stimulation techniques in geothermal reservoirs. Due to low injectivity, production rates from the Lithuanian field are currently reduced, which lead to negative commercial implications for the site. Productivity from the same wells is measured to be 40 times higher. Injectivity decline in aquifers is often related to clogging processes in spatially correlated highly permeable structures, which control the main flow volume. We subdivided clogging processes into (1) physical, (2) chemical, and (3) biological processes and studied them by analyzing fluid and solid samples as well as operational data. The methods we used are fluid and solid analyses in situ, in the laboratory and in experimental setups, statistical interpretation, and numerical modeling. Our results show that the spatially correlating nature of permeable structures is responsible for exponentially decreasing injectivity because few highly permeable zones clog rapidly by intruded particles. In particular, field operations cause changes of the physical, chemical, and biological processes in the aquifer. Mineral precipitation and corrosion are the main chemical processes observed at our site. Microbial activity causes biofilm while fines migration is caused by changes in physical boundary conditions. Moreover, these processes can affect each other and generate further reactions, for example, microbial activity triggers corrosion in surface pipelines.